A Bright Short Period M-M Eclipsing Binary from the KELT Survey: Magnetic Activity and the Mass–Radius Relationship for M Dwarfs - Lubin, Jack B. (2017)
We report the discovery of KELT J041621-620046, a moderately bright (J ? 10.2) M-dwarf eclipsing binary system at a distance of 39 ± 3 pc. KELT J041621-620046 was first identified as an eclipsing binary using observations from the Kilodegree Extremely Little Telescope (KELT) survey. The system has a short orbital period of ?1.11 days and consists of components with {M}1={0.447}+0.052-0.047 M⊙ and {M}2={0.399}+0.046-0.042 M⊙ in nearly circular orbits. The radii of the two stars are {R}1={0.540}+0.034-0.032 R⊙ and {ext{}}{R}2=0.453+/- 0.017 R⊙ . Full system and orbital properties were determined (to ?10% error) by conducting an EBOP (Eclipsing Binary Orbit Program) global modeling of the high precision photometric and spectroscopic observations obtained by the KELT Follow-up Network. Each star is larger by 17%-28% and cooler by 4%-10% than predicted by standard (non-magnetic) stellar models. Strong Hα emission indicates chromospheric activity in both stars. The observed radii and temperature discrepancies for both components are more consistent with those predicted by empirical relations that account for convective suppression due to magnetic activity.